2022
DOI: 10.1038/s41598-022-14773-y
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic pump with heat and mass transfer of a fractional second grade fluid through porous medium inside a tube

Abstract: In magnetic resonance imaging (MRI), this MRI is used for the diagnosis of the brain. The dynamic of these particles occurs under the action of the peristaltic waves generated on the flexible walls of the brain. Studying such fluid flow of a Fractional Second-Grade under this action is therefore useful in treating tissues of cancer. This paper deals with a theoretical investigation of the interaction of heat and mass transfer in the peristaltic flow of a magnetic field fractional second-grade fluid through a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Moreover, Padmaja et al [37] investigated a chemically reactive Cu-H 2 0 on MHD nanofluid swirl coating flow on a rotating vertical electrically insulated cone next to a porous medium in the presence of a radial static magnetic field. Several studies are also found in [38,39].…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, Padmaja et al [37] investigated a chemically reactive Cu-H 2 0 on MHD nanofluid swirl coating flow on a rotating vertical electrically insulated cone next to a porous medium in the presence of a radial static magnetic field. Several studies are also found in [38,39].…”
Section: Introductionmentioning
confidence: 89%
“…The peristaltic flow of fractional viscoelastic liquid has recently become significant due to its diverse applications in areas such as life science, physical science, and bioengineering. Recent studies also reported on the second-grade fluid with different geometry [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of skin irritation, hypertension, the eradication of harmful cancer cells, the dilution technique for assessing blood flow and paper manufacturing is just a few of the plethora of processes that are involved in heat transmission. The references [32][33][34][35][36][37][38][39][40][41][42][43] cover some useful studies in heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%